2013
DOI: 10.1371/journal.pone.0057793
|View full text |Cite
|
Sign up to set email alerts
|

Deltex-1 Activates Mitotic Signaling and Proliferation and Increases the Clonogenic and Invasive Potential of U373 and LN18 Glioblastoma Cells and Correlates with Patient Survival

Abstract: Glioblastoma (GBM) is a highly malignant primary tumor of the central nervous system originating in glial cells. GBM results in more years of life lost than any other cancer type. Low levels of Notch receptor expression correlates with prolonged survival in various high grade gliomas independent of other markers. Different downstream pathways of Notch receptors have been identified. We tested if the Notch/Deltex pathway, which is distinct from the canonical, CSL-mediated pathway, has a role in GBM. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 54 publications
(64 reference statements)
0
49
0
Order By: Relevance
“…Furthermore, DTX1 mutations that do not show an effect in the Notch1-mediated transcriptional activation of target genes might still be relevant in contexts of noncanonical Notch signaling. 54 We propose that the accumulation of deleterious mutations in DTX1, which were in general mutually exclusive with NOTCH1 and NOTCH2 mutations, constitute an additional mechanism by which B cells may acquire oncogenic Notch signaling in DLBCLs. The discovery that additional Notch signaling molecules are mutated in a relevant proportion of DLBCL might support the development of therapeutic strategies that target this pathway in DLBCL patients.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, DTX1 mutations that do not show an effect in the Notch1-mediated transcriptional activation of target genes might still be relevant in contexts of noncanonical Notch signaling. 54 We propose that the accumulation of deleterious mutations in DTX1, which were in general mutually exclusive with NOTCH1 and NOTCH2 mutations, constitute an additional mechanism by which B cells may acquire oncogenic Notch signaling in DLBCLs. The discovery that additional Notch signaling molecules are mutated in a relevant proportion of DLBCL might support the development of therapeutic strategies that target this pathway in DLBCL patients.…”
Section: Discussionmentioning
confidence: 94%
“…DTX1 on the other hand, functions as an ubiquitin binding protein and has been shown to function in B cell maturation [62]. However, over-expression of this protein can result in T cell anergy and can promote cancer proliferation [62,63]. The confirmation of these genes suggests that IL-15 promotes inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression profiles of GSE44561 (Guichet et al, 2015), GSE48079 (Garner et al, 2013) and GSE22772 (Huber et al, 2013) were downloaded from National Center of Biotechnology Information (NCBI) Gene Expression Omnibus (GEO) database (Barrett et al, 2005) (http://www.ncbi.nlm.gov/geo/). A total number of eight samples for GSE44561 with activated Notch signaling pathway by a forced expression of the Notch intracellular domain were available, including four embryonic human neural stem cells samples and four GBM samples, and the platform was GPL11532.…”
Section: Microarray Datamentioning
confidence: 99%
“…Doucas et al demonstrated that there were significant correlations between expression of Notch 3 and each of STAT3 and pSTAT3 in pancreatic adenocarcinomas (Doucas et al, 2008). DTX1 has been proved to be a cytoplasmic downstream element of Notch signaling pathway (Yamamoto et al, 2001), and over-expression of DTX1 increased cell migration and invasion correlating to endogenous Notch levels (Huber et al, 2013). MAML1, as a human homolog of the Drosophila mastermind, is proved to be a transcriptional co-activators for notch receptors (Wu et al, 2000) and the effects of activated Notch 1 on endothelial cell growth inhibition can be antagonized by upregulated expression of a dominant-negative mutant of MAML1 (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%